(untitled) (Journal of Asian Development Studies, 2015)
Research with children and young adults in safe environments is fraught enough, but the process of such research becomes rather more challenging when the children and youth are from migrant and refugee families. This research was conducted in Rawalpindi and Islamabad cities of Pakistan. An ethnographic approach was used to explore the daily lives of the Afghan and Pathan children and youth working on the streets. Access to the children and their families was initially made through different support organizations. A variety of qualitative participatory tools and techniques such as semi structured interviews, visual and observation techniques were used to gain and sustain the trust of the children and youth. These techniques also enabled useful rich data and an in-depth understanding of the children’s and youths’ daily lives, including the effectiveness of the support organizationsfor these disadvantaged young people. However, the worth of such tools and techniques varies according to circumstance, and they all need adaptation in different research settings.